Content Analysis of Moral Da'wah Messages on @basyasman00 TikTok Account - Mubaddilah Rafa’al; Syaifuddin Syaifuddin; Burhan Burhan; Rakhmat Rakhmat; Timo Kartinen (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the moral da'wah message on the TikTok @basyasman00 account by focusing on three categories of morals, namely morality to Allah, morality towards fellow creatures, and morality towards the environment. This study uses a quantitative approach with Scott's content analysis method. The research data was in the form of 27 da'wah videos uploaded in the January-July 2022 period and analyzed through a coding sheet. The encoding process is carried out by three coder, while the inter-coder reliability is tested using Scott's Pi. The results of the reliability test showed a value of 0.52 which was in the moderate category. The findings of the study show that moral messages to Allah are the most dominant category with 11 videos or 41%, followed by moral messages towards fellow creatures as many as 10 videos or 37%, and moral messages towards the environment as many as 6 videos or 22%. These results show that moral da'wah on @basyasman00 account emphasizes strengthening human spiritual relationships with God, while social and ecological messages emerge as supporting themes. This research confirms that TikTok can be a space for the distribution of short video-based moral da'wah, but digital da'wah practices need to expand the balance of themes to include spiritual, social, and environmental dimensions in a more proportionate manner.